Experimental analysis of Dynamic Charge Acceptance test conditions for lead-acid and lithium iron phosphate cells. (August 2017) - Smith, M J; Gladwin, D T; Stone, D A
Highlights: Direct comparison of DCA performance of lead-acid and lithium iron phosphate cells. Evaluation of effects of environmental factors and test conditions on DCA. Method for superior evaluation of DCA performance under real-world conditions. Abstract: This paper presents the results of a series of tests to determine the Dynamic Charge Acceptance (DCA) performance of small form-factor carbon-enhanced VRLA cells designed for use in Hybrid Electric Vehicle (HEV) applications, together with standard lead-acid and lithium iron phosphate (LFP) cells. The results demonstrate how varying the conditions and parameters of the standard DCA test regime can provide a superior evaluation of DCA performance and lead to a better understanding of cell behaviour under real-world conditions. A modified test procedure is proposed, based on the DCA Short Test profile (EN50342-6). Results are presented for a batch of carbon-enhanced cells, tested at various temperatures, rest periods and States of Charge (SoC) for the cell. These conditions having been chosen to mimic a range of real-life scenarios which could potentially be encountered during HEV operation. The resulting analysis demonstrates clear variations and trends in DCA performance which may be used to inform conditions for future testing regimes. The modified test procedure is then applied to standard lead-acid and LFP 26650-type cells and the results compared.